Dynamic analysis of aircraft landing gear - Yengejeh, Sadegh Imani (2013)
Landing gear dynamics, especially shimmy and break-induced vibrations, is one of the problems faced today by the aircraft community. Landing gear vibration may lead to fatal accidents due to excessive wear; it can also shorten the gear life, and affect comfort to the pilot and passengers. Among the most important reasons for landing gear vibrations are unsuitable combination of structural stiffness, damping, and pneumatic tire characteristics furthermore an unlucky combination of brake system design with the tire physics can produce a serious vibration problem. Many available computer-aided engineering tools and software have made it possible to test some of the problems in the design phase by simulating the landing gear impact and ground maneuvers. In this study, it has been conducted to simulate the simplified model of aircraft Eagle-150 in MSC. ADAMS software and work on the simulation of such an unstable and complex phenomenon during landing position and also aircraft ground maneuver in order to detect vibrations in aircraft landing gear. It has also been tried to study the effect of important parameters that may affect the instability and comfort a simple simulated model of aircraft and its landing gear was prepared using ADAMS for this purpose. An adequate model of aircraft and landing gear is an important aspect of analysis in order to understand the behavior of an aircraft during landing and ground maneuver. Effect of various parameters on landing gear vibration is also one the purposes of this study.